Colloidal complexation of zein hydrolysate with tannic acid: Constructing peptides-based nanoemulsions for alga oil delivery. (March 2016) - Wang, Yong-Hui; Wan, Zhi-Li; Yang, Xiao-Quan; Wang, Jin-Mei; Guo, Jian; Lin, Yuan
Abstract: Colloidal complexation of zein hydrolysate (ZH) with tannic acid (TA) and the possibility of using the ZH-TA complex to construct a nanoemulsion system for alga oil delivery were investigated. Turbidity and fluorescence titration measurements demonstrated the complexation of ZH with TA, which leads to the formation of ZH-TA complex. Isothermal titration calorimetry further confirmed the complexation between ZH and TA was driven by the non-covalent interaction (e.g. hydrophobic interaction and hydrogen bonding). The emulsifying activity of ZH was considerably improved after the complexation with TA, which was responsible for the fabrication of alga oil nanoemulsions ( d  = 120 nm). The emulsions stabilized by the ZH-TA complex showed a remarkable physical stability and high alga oil encapsulation efficiency. More importantly, the complexation of ZH with TA also endowed ZH-TA complex with high antioxidative properties. The alga oil nanoemulsions stabilized by ZH-TA complex showed an increased oxidative stability with reduced lipid hydroperoxides and volatile hexanal compared with that of stabilized by ZH alone. This study demonstrated that ZH-TA complex could be employed as an emulsifier in constructing a physical stable nanoemulsion delivery system, and opens up the possibility of utilizing peptides–polyphenol complex as efficient emulsifiers to improve the oxidative stability of O/W nanoemulsions. Graphical abstract: Highlights: Confirmed colloidal complexation of zein hydrolysate (ZH) with tannic acid (TA). The complexation with TA made the emulsifying activity of ZH greatly improved. The alga oil nanoemulsions ( d  = 120 nm) showed long-term stability after 4 weeks. The emulsions stabilized by ZH-TA complex showed an improved oxidative stability.